![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\left(x^3-x^2\right)-4x^2+8x-4=0\)
\(\Leftrightarrow x^3-x^2-4x^2+8x-4=0\)
\(\Leftrightarrow x^3-5x^2+8x-4=0\)
\(\Leftrightarrow x^3-x^2-4x^2+4x+4x-4=0\)
\(\Leftrightarrow x^2\left(x-1\right)-4x\left(x-1\right)+4\left(x-1\right)=0\)
\(\Leftrightarrow\left(x-1\right)\left(x^2-4x+4\right)=0\)
\(\Leftrightarrow\left(x-1\right)\left(x-2\right)^2=0\)
\(\Leftrightarrow\orbr{\begin{cases}x-1=0\\\left(x-2\right)^2=0\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x=1\\x-2=0\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x=1\\x=2\end{cases}}\)
Vậy ...
\(\left(x^3-x^2\right)-4x^2+8x-4=0\)
\(\Leftrightarrow x^3-x^2-4x^2+8x-4=0\)
\(\Leftrightarrow x^3-x^2-4x^2+4x+4x-4=0\)
\(\Leftrightarrow\left(x^3-x^2\right)-\left(4x^2+4x\right)+\left(4x-4\right)=0\)
\(\Leftrightarrow x^2\left(x-1\right)-4x\left(x-1\right)+4\left(x-1\right)=0\)
\(\Leftrightarrow\left(x-1\right)\left(x^2-4x+4\right)=0\)
\(\Leftrightarrow\left(x-1\right)\left(x-2\right)^2=0\)
\(\Leftrightarrow\orbr{\begin{cases}x-1=0\\x-2=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x=1\\x=2\end{cases}}}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
(x2 + x + 1)(6 - 2x) = 0
<=> 6 - 2x = 0 (do x2 + x + 1 > 0)
<=> 2x = 6
<=> x = 3
Vậy S = {3}
(8x - 4)(x2 + 2x + 2) = 0
<=> 8x - 4 = 0 (vì x2 + 2x + 2 > 0)
<=> 8x = 4
<=> x = 1/2
Vậy S = {1/2}
x3 - 7x + 6 = 0
<=> x3 - x - 6x + 6 = 0
<=> x(x2 - 1) - 6(x - 1) = 0
<=> x(x - 1)(x + 1) - 6(x - 1) = 0
<=> (x2 + x - 6)(x - 1) = 0
<=> (x2 + 3x - 2x - 6)(x - 1) = 0
<=> (x + 3)(x - 2)(x - 1) = 0
<=> x + 3 = 0
hoặc x - 2 = 0
hoặc x - 1 = 0
<=> x = -3
hoặc x = 2
hoặc x = 1
Vậy S = {-3; 1; 2}
x5 - 5x3 + 4x = 0
<=> x(x4 - 5x2 + 4) = 0
<=> x(x4 - x2 - 4x2 + 4) = 0
<=> x[x2(x2 - 1) - 4(x2 - 1)] = 0
<=> x(x - 2)(x + 2)(x - 1)(x + 1) = 0
<=> x = 0 hoặc x - 2 = 0 hoặc x + 2 = 0 hoặc x - 1 = 0 hoặc x + 1 = 0
<=> x = 0 hoặc x = 2 hoặc x = -2 hoặc x = 1 hoặc x = -1
Vậy S = {-2; -1; 0; 1; 2}
+ Ta có: \(\left(x^2+x+1\right).\left(6-2x\right)=0\)
- Ta lại có: \(x^2+x+1=\left(x^2+x+\frac{1}{4}\right)+\frac{3}{4}=\left(x+\frac{1}{2}\right)^2+\frac{3}{4}\ge\frac{3}{4}>0\forall x\)
- Vì \(x^2+x+1>0\forall x\)mà \(\left(x^2+x+1\right).\left(6-2x\right)=0\)
\(\Rightarrow6-2x=0\Leftrightarrow-2x=-6\Leftrightarrow x=3\left(TM\right)\)
Vậy \(S=\left\{3\right\}\)
+ Ta có: \(\left(8x-4\right).\left(x^2+2x+2\right)=0\)
- Ta lại có: \(x^2+2x+2=\left(x^2+2x+1\right)+1=\left(x+1\right)^2+1\ge1>0\forall x\)
- Vì \(x^2+2x+2>0\forall x\)mà \(\left(8x-4\right).\left(x^2+2x+2\right)=0\)
\(\Rightarrow8x-4=0\Leftrightarrow8x=4\Leftrightarrow x=\frac{1}{2}\left(TM\right)\)
Vậy \(S=\left\{\frac{1}{2}\right\}\)
+ Ta có: \(x^3-7x+6=0\)
\(\Leftrightarrow\left(x^3-x^2\right)+\left(x^2-x\right)+\left(6x-6\right)=0\)
\(\Leftrightarrow\left(x-1\right).\left(x^2+x-6\right)=0\)
\(\Leftrightarrow\left(x-1\right).\left[\left(x^2-2x\right)+\left(3x-6\right)\right]=0\)
\(\Leftrightarrow\left(x-1\right).\left(x-2\right).\left(x+3\right)=0\)
Vậy \(S=\left\{-3;1;2\right\}\)
+ Ta có: \(x^5-5x^3+4x=0\)
\(\Leftrightarrow x.\left[\left(x^4-x^2\right)-\left(4x^2-4\right)\right]=0\)
\(\Leftrightarrow x.\left[x^2.\left(x^2-1\right)-4.\left(x^2-1\right)\right]=0\)
\(\Leftrightarrow x.\left(x^2-1\right).\left(x^2-4\right)=0\)
\(\Leftrightarrow x=0\left(TM\right)\)
hoặc \(x^2-1=0\Leftrightarrow x^2=1\Leftrightarrow x=\pm1\left(TM\right)\)
hoặc \(x^2-4=0\Leftrightarrow x^2=4\Leftrightarrow x=\pm2\left(TM\right)\)
Vậy \(S=\left\{-2;-1;0;1;2\right\}\)
!!@@# ^_^ Chúc bạn hok tốt ^_^#@@!!
![](https://rs.olm.vn/images/avt/0.png?1311)
1. \(\frac{7x-1}{6}+2x=\frac{16-x}{5}\)
\(\Leftrightarrow5\left(7x-1\right)+60x=6\left(16-x\right)\)
\(\Leftrightarrow35x-5+60x=96-6x\)
\(\Leftrightarrow95x-5=96-6x\)
\(\Leftrightarrow95x+6x=96+5\)
\(\Leftrightarrow101x=101\)
\(\Leftrightarrow x=1\)
2. \(\frac{10x+3}{12}=1+\frac{6+8x}{9}\)
\(\Leftrightarrow3\left(10x+3\right)=36+4\left(6+8x\right)\)
\(\Leftrightarrow30x+9=36+24+32x\)
\(\Leftrightarrow30x+9=32x+60\)
\(\Leftrightarrow30x-32x=60-9\)
\(\Leftrightarrow-2x=51\)
\(\Leftrightarrow x=-\frac{51}{2}\)
3. \(\frac{8x-3}{4}-\frac{3x-2}{2}=\frac{2x-1}{2}+\frac{x+3}{4}\)
\(\Leftrightarrow8x-3-2\left(3x-2\right)=2\left(2x-1\right)+x+3\)
\(\Leftrightarrow8x-3-6x+4=4x-2+x+3\)
\(\Leftrightarrow2x+1=5x+1\)
\(\Leftrightarrow2x=5x\)
\(\Leftrightarrow x=0\)
4) \(\frac{3\left(3-x\right)}{8}+\frac{2\left(5-x\right)}{3}=\frac{1-x}{2}-2\)
=> \(\frac{9-3x}{8}+\frac{10-2x}{3}=\frac{1-x}{2}-\frac{2}{1}\)
=> \(\frac{3\left(9-3x\right)}{24}+\frac{8\left(10-2x\right)}{24}=\frac{12\left(1-x\right)}{24}-\frac{48}{24}\)
=> \(\frac{27-9x}{24}+\frac{80-16x}{24}=\frac{12-12x}{24}-\frac{48}{24}\)
=> \(\frac{27-9x+80-16x}{24}=\frac{12-12x-48}{24}\)
=> 27 - 9x + 80 - 16x = 12 - 12x - 48
=> 27 - 9x + 80 - 16x - 12 + 12x + 48 = 0
=> (27 + 80 - 12 + 48) + (-9x - 16x + 12x) = 0
=> 143 - 13x = 0
=> 13x = 143
=> x = 11
5) \(\frac{2\left(x-3\right)}{7}+\frac{x-5}{3}-\frac{13x+4}{21}=0\)
=> \(\frac{2x-6}{7}+\frac{x-5}{3}-\frac{13x+4}{21}=0\)
=> \(\frac{3\left(2x-6\right)}{21}+\frac{7\left(x-5\right)}{21}-\frac{13x+4}{21}=0\)
=> \(\frac{6x-18}{21}+\frac{7x-35}{21}-\frac{13x+4}{21}=0\)
=> \(\frac{6x-18+7x-35-13x-4}{21}=0\)
=> 6x - 18 + 7x - 35 - 13x - 4 = 0
=> (6x + 7x - 13x) + (-18 - 35 - 4) = 0
=> -57 = 0(vô nghiệm)
6) \(\frac{6x+5}{2}-\left(2x+\frac{2x+1}{2}\right)=\frac{10x+3}{4}\)
=> \(\frac{6x+5}{2}-\frac{10x+3}{4}=2x+\frac{2x+1}{2}\)
=> \(\frac{2\left(6x+5\right)}{4}-\frac{10x+3}{4}=\frac{8x}{4}+\frac{2\left(2x+1\right)}{4}\)
=> \(\frac{12x+10}{4}-\frac{10x+3}{4}=\frac{8x}{4}+\frac{4x+2}{4}\)
=> \(\frac{12x+10-\left(10x+3\right)}{4}=\frac{8x+4x+2}{4}\)
=> \(\frac{12x+10-10x-3}{4}=\frac{12x+2}{4}\)
=> \(12x+10-10x-3=12x+2\)
=> \(2x+10-3=12x+2\)
=> 2x + 10 - 3 - 12x - 2 = 0
=> (2x - 12x) + (10 - 3 - 2) = 0
=> -10x + 5 = 0
=> -10x = -5
=> x = 1/2
7) \(\frac{2x-1}{5}-\frac{x-2}{3}-\frac{x+7}{15}=0\)
=> \(\frac{3\left(2x-1\right)}{15}-\frac{5\left(x-2\right)}{15}-\frac{x+7}{15}=0\)
=> \(\frac{6x-3}{15}-\frac{5x-10}{15}-\frac{x+7}{15}=0\)
=> \(\frac{6x-3-\left(5x-10\right)-\left(x+7\right)}{15}=0\)
=> 6x - 3 - 5x + 10 - x - 7 = 0
=> (6x - 5x - x) + (-3 + 10 - 7) = 0
=> 0x + 0 = 0
=> 0x = 0
=> x tùy ý
Bài 8 tự làm nhé
![](https://rs.olm.vn/images/avt/0.png?1311)
b)\(3x^3+6x^2-75x-150=0\Leftrightarrow3\left(x^3+2x^2-25x-50\right)=0\Leftrightarrow x^3+2x^2-25x-50=0\)
<=>\(x^2\left(x+2\right)-25\left(x+2\right)=0\Leftrightarrow\left(x^2-25\right)\left(x+2\right)=0\Leftrightarrow\left(x-5\right)\left(x+5\right)\left(x+2\right)=0\)
<=>x-5=0 hoặc x+5=0 hoặc x+2=0<=>x=5 hoặc x=-5 hoặc x=-2
c)\(2x^5-3x^4+6x^3-8x^2+3=0\Leftrightarrow2x^5+x^4-4x^4-2x^3+8x^3+4x^2-12x^2+3=0\)
<=>\(x^4\left(2x+1\right)-2x^3\left(2x+1\right)+4x^2\left(2x+1\right)-3\left(4x^2-1\right)=0\)
<=>\(x^4\left(2x+1\right)-2x^3\left(2x+1\right)+4x^2\left(2x+1\right)-3\left(2x-1\right)\left(2x+1\right)=0\)
<=>\(\left(2x+1\right)\left(x^4-2x^3+4x^2-6x+3\right)=0\)
<=>\(\left(2x+1\right)\left(x^4-2x^3+x^2+3x^2-6x+3\right)=0\)
<=>\(\left(2x+1\right)\left[x^2\left(x^2-2x+1\right)+3\left(x^2-2x+1\right)\right]=0\)
<=>\(\left(2x+1\right)\left(x^2+3\right)\left(x^2-2x+1\right)=0\Leftrightarrow\left(2x+1\right)\left(x^2+3\right)\left(x-1\right)^2=0\)
Vì \(x^2\ge0\Rightarrow x^2+3\ge3>0\Rightarrow\orbr{\begin{cases}2x+1=0\\\left(x-1\right)^2=0\end{cases}}\Rightarrow\orbr{\begin{cases}x=-\frac{1}{2}\\x=1\end{cases}}\)
a) 2x3 - x2 - 8x + 4 = 0
x2.(2x - 1) - 4.(2x - 1) = 0
(x2 - 4)(2x - 1) = 0
\(\Rightarrow\orbr{\begin{cases}x^2-4=0\\2x-1=0\end{cases}}\Rightarrow\orbr{\begin{cases}x^2=4\\x=\frac{1}{2}\end{cases}}\)
Với x2 = 4
=> x = 2 hoặc x = -2
=> x = {-2 ; 2 ; \(\frac{1}{2}\))
\(x^4-4x^3+8x-5=0\)
\(\Leftrightarrow x^4-x^3-3x^3+3x^2-3x^2+3x+5x-5=0\)
\(\Leftrightarrow x^3\left(x-1\right)-3x^2\left(x-1\right)-3x\left(x-1\right)+5\left(x-1\right)=0\)
\(\Leftrightarrow\left(x-1\right)\left(x^3-3x^2-3x+5\right)=0\)
\(\Leftrightarrow\left(x-1\right)\left(x^3-x^2-2x^2+2x-5x+5\right)=0\)
\(\Leftrightarrow\left(x-1\right)\left[x^2\left(x-1\right)-2x\left(x-1\right)-5\left(x-1\right)\right]=0\)
\(\Leftrightarrow\left(x-1\right)^2\left(x^2-2x-5\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x-1=0\\x^2-2x-5=0\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x=1\\x^2-2x+1=6\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x=1\\\left(x-1\right)^2=6\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x=1\\x-1=\pm\sqrt{6}\end{cases}}\)
\(\Leftrightarrow\orbr{\begin{cases}x=1\\\orbr{\begin{cases}x-1=\sqrt{6}\\x-1=-\sqrt{6}\end{cases}}\end{cases}}\)\(\Leftrightarrow\orbr{\begin{cases}x=1\\x=\pm\sqrt{6}+1\end{cases}}\)
Vậy...
x4 - 4x3 + 8x - 5 = 0
<=> x4 - x3 - 3x3 + 3x2 - 3x2 + 3x + 5x - 5 = 0
<=> x3( x - 1 ) - 3x2( x - 1 ) - 3x( x - 1 ) + 5( x - 1 ) = 0
<=> ( x - 1 )( x3 - 3x2 - 3x + 5 ) = 0
<=> ( x - 1 )( x3 - x2 - 2x2 + 2x - 5x + 5 ) = 0
<=> ( x - 1 )[ x2( x - 1 ) - 2x( x - 1 ) - 5( x - 1 ) ] = 0
<=> ( x - 1 )2( x2 - 2x - 5 ) = 0
<=> x - 1 = 0 hoặc x2 - 2x - 5 = 0
+) x - 1 = 0 <=> x = 1
+) x2 - 2x - 5 = 0
<=> ( x2 - 2x + 1 ) - 6 = 0
<=> ( x - 1 )2 - ( √6 )2 = 0
<=> ( x - 1 - √6 )( x - 1 + √6 ) = 0
<=> x = 1 + √6 hoặc x = 1 - √6
Vậy S = { 1 ; 1 ± √6 }